1994
DOI: 10.1016/0014-5793(94)00698-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of different mitogen‐regulated protein/proliferin mRNAs in Ehrlich carcinoma cells

Abstract: Results from in vivo and from serum-free primary cultures of Ehrlich cells suggest that the expression of mitogen-regulated protein/proliferin (MRP/PLF) mRNAs is not essential for proliferation of this murine tumor. Two sizes for MRP/PRL-related open reading frames (ORFs) have been detected by reverse transcription/PCR amplification. They are almost identical to that reported for PLF-1; but 20% of the amplified cDNA included a shorter ORF, which lacks the entire sequence corresponding to that of the exon 3 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…We further established Plf‐1 KO cells by introducing a CRISPR‐Cas9 targeting vector into FM3A and Ehrlich tumor cells and also established cell transformants in which Plf‐1 was re‐expressed in Plf‐1 KO cells (Figure 3D). As previous reports have indicated that PLF‐1 regulates cell proliferation of neuroblastoma, but not that of Ehrlich tumor cells, 21,29 we evaluated the effect of Plf‐1 expression levels on cell proliferation and confirmed that neither deficiency nor re‐expression of Plf‐1 had affected the cell proliferation of FM3A and Ehrlich tumor cell lines (Supplemental Figure 3B). We next collected culture supernatants from these cells and compared their effects on adipogenesis.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…We further established Plf‐1 KO cells by introducing a CRISPR‐Cas9 targeting vector into FM3A and Ehrlich tumor cells and also established cell transformants in which Plf‐1 was re‐expressed in Plf‐1 KO cells (Figure 3D). As previous reports have indicated that PLF‐1 regulates cell proliferation of neuroblastoma, but not that of Ehrlich tumor cells, 21,29 we evaluated the effect of Plf‐1 expression levels on cell proliferation and confirmed that neither deficiency nor re‐expression of Plf‐1 had affected the cell proliferation of FM3A and Ehrlich tumor cell lines (Supplemental Figure 3B). We next collected culture supernatants from these cells and compared their effects on adipogenesis.…”
Section: Resultssupporting
confidence: 65%
“…18,19,28 Although all members of PLFs share high amino acid sequence similarity, 18 we found that only PLF-1 could strongly suppress the droplet accumulation of preadipocytes. A previous study suggested that various Plf mRNAs were expressed in Ehrlich cells, 29 but we found that PLF-1 expression was dominant in Ehrlich and FM3A…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…An angiogenic phenotype in bovine papillomavirus type 1‐induced murine fibrosarcoma cells appears to be in part a result of secreted PLF1 protein [18]. Immortalized cell lines and tumor‐derived cell lines often express mrp/plf ‐ M rna; and MRP/PLF proteins may contribute to an autocrine stimulation for in vitro cell proliferation [19–21]. Low levels of mrp3 ‐mRNA and MRP/PLF protein are induced in murine epidermal cells after skin wounding and both plf1 and mrp3 ‐mRNAs and MRP/PLF proteins were found in follicular root sheath cells after hair growth was initiated by wax‐rosin depilation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mitogen regulated proteins/Proliferins (MRP/PLF's) are a family of glycoproteins that are secreted by cells in response to mitogen/growth factor stimulation [213]. MRP/PLFs can be produced by the following mouse cell lines: BALB/c 3T3 [214] [215], BNL [216], Krebs ascites carcinoma cells [217], IOTl/2 cells [218J and Ehrlich ascites carcinoma cells [219].…”
Section: Mitogen Regulated Protein/proliferin'smentioning
confidence: 99%